-49-7b=-42

Simple and best practice solution for -49-7b=-42 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -49-7b=-42 equation:


Simplifying
-49 + -7b = -42

Solving
-49 + -7b = -42

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + -7b = -42 + 49

Combine like terms: -49 + 49 = 0
0 + -7b = -42 + 49
-7b = -42 + 49

Combine like terms: -42 + 49 = 7
-7b = 7

Divide each side by '-7'.
b = -1

Simplifying
b = -1

See similar equations:

| 22=2x+2y | | 8=b-1+8 | | q^2-10q-17=0 | | -2.6-11.2= | | -10+10r=80 | | -z+16z-15z+9z=-9 | | 3x-6+3x-6+2x+2+2x+2=142 | | 7x+14=42 | | (130-x)+x=130 | | -6x+x=-2-6(-12x-13) | | (20÷4*2÷5-1)/(-9(-3)-12÷3) | | x^2-43560=0 | | 17j-9j-7j=13 | | m^2+26m-37=0 | | 7c+4c+5c-15c=8 | | 3x+6+2x+4+4x-2=126 | | 20x+13=21x+9 | | p^2-10p-39=0 | | 7s-5s-s=9 | | 4d+7=3d+15 | | C(4,1)*(5/25)*(20/25)^3 | | -3x^2+2xy=0 | | 8p-7p=17 | | x^3-6y^2-9y^1=0 | | 2.5-2.5x=-3 | | 2x+7-3=-8+x+7+2x | | 6cos^2x=3+3sinx | | 10j-4j=18 | | 12+7x=2(x+6)+5x | | 3(x-3)=-0.6 | | 8y-2x=2x-y | | 1.6n-72=4n-30 |

Equations solver categories